We need to accelerate the digitization of existing botanical information and complete the global plant inventory. Issue 1 (4th December 2022) - Corlett, Richard T.
Abstract: The availability of a global checklist of known land plants makes it possible to bring together all botanical information and make it accessible online. Two obstacles remain, however. First, most existing information is not yet digitized. Second, an estimated 10%‒25% more species are still undescribed and therefore invisible to science. 摘要: 完成全世界已知陆生植物的名录并在线发布，将能整合全世界的植物信息。然而，仍然有两方面的因素阻碍这一目标的实现。第一，绝大多数现有的信息还未被数字化。第二，至少约10%‒25%的物种还未被发表，从而不为科学界认识。